Safety and Blood-Flow Outcomes for Hybrid Recanalization in Symptomatic Refractory Long-Segmental Vertebral Artery Occlusion—Results of a Pilot Study - Ma, Yan; Yang, Bin; Lu, Xia; Gao, Peng; Jiao, Liqun; Ling, Feng (Frontiers in Neurology, 2020)
Objective: Hybrid recanalization for vertebral artery (VA) long-segmental occlusion using a combination of ostial vertebral endarterectomy and distal endovascular stenting has achieved technical success. The safety and efficacy of the hybrid technique should be further evaluated. Methods: We examined a cohort of refractory patients with long-segmental occlusion in the VA and low flow in the basilar artery (BA). The hybrid technique was performed to achieve the recanalization of VA. Angiograms were analyzed for occlusive length, contralateral VA status and collaterals. Clinical variables, including 30-days outcomes and blood-flow changes within 6 months based on quantitative magnetic resonance angiography (qMRA) with non-invasive optimal vessel analysis (NOVA), were collected pre- and post-operatively. Results: Among 290 consecutive cases with VA initial segment stenosis or occlusion, 14 patients (13 male and 1 female) with symptomatic long-segmental VA occlusion and low flow in the BA were refractory to the best standard medical therapy. The hybrid technique was successful in obtaining recanalization in all but one patient. The mean follow-up period was 17.2 ± 9.2 months. One patient had new ischemic deficits within seven days of the operation. Four patients suffered from transient Horner syndrome postoperatively, but had recovered completely by the 6-months follow-up. Within this period, all revascularization was visible with computed tomography angiography (CTA), and the blood-flow in the BA improved significantly (66.4 ± 15.3 ml/min vs. 104.0±12.9 ml/min, P < 0.05) within 6 months. No ischemic events recurred during follow-up. Conclusions: The hybrid technique is potentially a safe and feasible method to achieve recanalization and improve hemodynamic compromise for long-segmental VA occlusion.